Disclosure of Bank Product Information and the Principle of Bank Secrecy: A Legal Analysis of Customer Protection in Indonesia - Alvin Hamzah Nasution; Sugih Ayu Pratitis (Rechtsvinding, 2026)
This study examines the legal issues between the obligation to transparency in banking products and the protection of customer confidentiality in the Indonesian legal system. Information disclosure is necessary to guarantee consumers' rights to obtain adequate explanations regarding the benefits, costs, and risks of bank products, while bank confidentiality serves to maintain the security of customer data. Using a normative juridical method through statutory, conceptual, and case approaches, this study is analyzed using the theories of justice, legal certainty, and consumer protection. The results of the study indicate that regulations regarding transparency in banking products are available in the Banking Law and OJK regulations, but their implementation has not fully placed customers on an equal footing with banks. The main obstacles lie in differences in public understanding and the lack of uniform standards for conveying product information. Therefore, regulatory harmonization, strengthening of market behavior supervision by the OJK, and the development of simpler information standards are needed to improve customer protection and public trust in the banking sector.